THE MAKING OF PROFILE VIDEO OF ZAPIN DANCE - Yesi Clara Siska Rumapea; Aswandi Aswandi (INOVISH JOURNAL, 2017)
Abstract: Bengkalis is one of the districts in Riau Province, Indonesia. One of heritage from Bengkalis  culture named Zapin dance. Zapin dance was originally brought from Yaman by merchants in early 16th century and this dance also educative entertainment. The advanced of technology develop this Zapin dance in the form  of video as media. The available videos on website only show the movement of the dance and this video show the history of the dance in Bahasa Indonesia. Therefore, the writer is interested in making of profile video of Zapin dance in English. Zapin dance was made as attractive as possible different from other videos and when people watch this video, they will be not bored. Besides that, this video not only can be used in Indonesia but abroad especially for foreigner who learns Zapin. This video equipped with profile pictures Zapin dance and types of Zapin Dance. For the tourism department, profile video of Zapin dance can help departments to  promote Zapin dance for whole society not only in Bengkalis but abroad. Keywords: Bengkalis, Video Profile, Zapin Dance